Protein kinase inhibitors in renal cell carcinoma. (February 2014) - Daste, Amaury; Grellety, Thomas; Gross-Goupil, Marine; Ravaud, Alain
<x xml:space="preserve">Abstract</x> Introduction: Metastatic Renal Cell Carcinoma (mRCC) was historically treated with cytokine therapy with a poor outcome. In the last decade, new therapies targeting vascular endothelial growth factor (VEGF) or the mammalian target of rapamycin (m-TOR) pathways demonstrated efficacy in mRCC. Protein kinase inhibitors as well as monoclonal antibodies targeting these pathways have become the standard treatment of renal cell carcinoma (RCC) in the first-line setting and beyond. Areas covered: This review describes the various Phase III trials concerning protein kinase inhibitors including anti-angiogenic tyrosine kinase inhibitors (TKIs) and m-TOR serine/threonine kinase inhibitors, which have demonstrated a benefit in the treatment of mRCC. It focuses on efficacy, safety and management. Expert opinion: VEGF TKI and m-TOR inhibitors have significantly improved the outcome of mRCC and offer a gain in survival by sequential treatments for the majority of patients. But they induce a particular toxicity profile. An adequate management of each drug and its sequence in treatment is essential to optimise the outcome and preserve the quality of life (QoL) of patients with mRCC. In forthcoming years, pending results should indicate whether VEGF TKI are of interest in an adjuvant setting and if new drugs targeting will challenge the current standard guidelines in the metastatic setting.